Strategi Efisiensi Konsumsi Listrik di RS Pertamina Panorama Balikpapan dengan Metode Fuzzy Logic - Romilado, Fither; Effendi, Yunus; Astharini, Dwi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Hospitals play a vital role in providing promotive, preventive, curative, and rehabilitative healthcare services. The highest electricity consumption in hospitals comes from lighting and air conditioning systems, thus requiring the implementation of an energy efficiency culture and appropriate technology selection to achieve environmentally friendly (green hospital) operations. This study aims to analyze the potential of applying energy efficiency culture and technology selection as well as to recommend strategies for reducing operational costs and developing energy-saving SOPs as part of green hospital practices. The fuzzy logic approach was applied to measure the level of energy efficiency at Pertamina Panorama Hospital Balikpapan, considering technological, electrical, mechanical and operational cost indicators. Data were collected from questionnaires distributed to 70 hospital staff to evaluate how energy-saving culture and technology choices support green hospital implementation. The results show that the adoption of technologies such as BMS, Smart Energy, Smart Material, Smart Water, Smart Waste, IEQ and Resilience & Safety reduced maintenance costs by 10–20%, despite an initial investment increase of 5–15%. The centroid fuzzy logic analysis yielded a crisp value of 84.7%, indicating efficient electricity consumption. The synergy between efficiency culture, modern technology, and cost strategies makes hospitals more energy-efficient, environmentally friendly and sustainable.Keywords - Efisiensi Energi, Fuzzy Logic, Green Building, Green Hospital.